Excellent bonding behaviour of novel surface-tailored fibre composite rods with cementitious matrix - Cunha, Fernando Eduardo Macedo (2014)
Novel composite rods were produced by a special braiding technique that involves braiding of polyester yarns around a core of resin-impregnated carbon fibres and subsequent curing. The surface roughness of these braided rods was tailored by replacing one or two simple yarns in the outer-braided layer with braided yarns (produced from 8 simple yarns) and adjusting the take-up velocity. Pull-out tests were carried out to characterize the bond behaviour of these composite rods with cementitious matrix. It was observed that the rod produced with two braided yarns in the outer cover and highest take-up speed was ruptured completely before pull-out, leading to full utilization of its tensile strength, and exhibited 134% higher pull-out force as compared to the rods produced using only simple braiding yarns.